(untitled) (Journal SCIENCEVOLUTION, 2024)
A didactic proposal is presented in response to the institutional demand to contribute to meaningful learning of physics concepts among 40 kinematics students in their second semester at Preparatoria 25 of the Universidad Autónoma de Nuevo León, Mexico (UANL). This qualitative, action-research study emphasized the principles of socioformation and was conducted using the ACODESA methodology (Collaborative Learning, Scientific Debate, and Self-reflection), virtual experimentation through the GeoGebra and PhET platform, interviews and surveys. It was identified that students developed the ability to use logic in discussions, justify their answers, and reach individual and group conclusions. Moreover, the approach enhanced the understanding of kinematic concepts and significantly facilitated the teaching process of kinematics. Learning mediated by virtual experimentation and the ACODESA methodology reduced failure rates compared to the three previous academic periods, with a notable 50% decrease in the Ordinary Failure Rate. It is recommended to implement the Action Plan Proposal and the Evaluation of Virtual Experimentation Results to promote meaningful learning of kinematics among physics students in upper-secondary educational institutions (NMS).